Analisis Sistem Antrian pada Proses Penimbangan dan Sortasi TBS di PT RKM - Iing Pamungkas; Heri Tri Irawan; Mahmud Basuki; Rizki Agam Syahputra; Viktor Mawar Berutu (Jurnal Industri dan Inovasi (INVASI), 2026)
Within the palm oil industry, the process of weighing and sorting Fresh Fruit Bunches (FFB) at the beginning of the supply chain is crucial for determining the price and quality of palm oil. However, PT RKM, a palm oil processing company in Aceh Singkil, faces challenges such as potential inaccuracies in weight measurement, quality classification, and long queues that can reduce operational efficiency. These issues have the potential to cause financial losses and production delays. The objective of this study is to measure and analyze the queuing system in the FFB weighing and sorting process at PT RKM. This research uses a queuing model approach to evaluate the current system's efficiency. Data were collected through direct observation and interviews, with 30 samples of truck arrival and service times. The analysis method used includes creating an Activity Cycle Diagram (ACD), calculating the average inter-arrival and service times, and determining system performance metrics such as average waiting time and server idle percentage.The results of the study show that the PT RKM queuing system operated optimally on the day of observation. The average queue waiting time was zero, and the percentage of idle servers (weighing facilities) was also zero. This indicates that the current service capacity is adequate for the volume of vehicle arrivals, thereby minimizing losses and improving overall productivity.